MANAJEMEN KELAS SEBAGAI UPAYA MENINGKATKAN KUALITAS PROSES BELAJAR MENGAJAR - Widiharto Purnomo (Program Studi Manajemen Pendidikan, FKIP Universitas Palangka Raya, 2022)
This study aims to identify and describe classroom management, in terms of: (1) planning, (2) organizing, (3) actuatin/implementing, and (4) controlling, as an effort to improve the quality of the teaching and learning process. Using a qualitative approach, data were collected using interview, observation, and documentation techniques. The data sources in this study were the Principal and 10 Teachers. Data analysis in this study uses an interactive model through the stages of data condensation, data presentation, and drawing conclusions (Miles et al, 2014). Validation of the data in this study using source triangulation techniques. Results showed that in general the classroom management implemented at SMPN 2 Palangka Raya went well and was able to improve the quality of the teaching and learning process as well as have an impact on improving student learning outcomes.